Development of a Meaningful Learning Model Based on Fishermen's Environment to Form Students' Creative Behavior - Nunu Nurfirdaus; Enok Maryani; Didin Saripudin; Wawan Darmawan (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2026)
The purpose of this research is to develop of a meaningful learning model based on fishermen’s environment to form students' creative behavior. This research is designed based on ADDIE development model. The population in this study were all junior high school students in coastal Cirebon. Data collection techniques used in this study include observation, interview, and lift distribution. Researchers will process and analyze the data using descriptive statistical analysis.  Data analysis was carried out in three stages during this study, namely data analysis during preliminary studies (empirical studies and literature studies), then data analysis during the design model development process, and finally, data analysis as a process of producing model effectiveness test results. Based on the results of this study, a meaningful learning model based on the fishing environment can increase the creativity of Cirebon coastal junior high school students.  This model connects new knowledge with what students already know, making the material easier to understand and encouraging creativity.